Experience report of nursing students in a supervised curricular internship in the COVID-19 pandemic context - Amanda Conrado Silva Barbosa; Hanna Cristina Ferreira; Liodany Rutherlem dos Santos Oliveira; Leticia Ferreira França Nicácio; Lucimar Borges de Oliveira; Yasmin Chagas do Carmo; Rafaela Dias Pardini (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2022)
Objective: To report Nursing students' experience during a curricular internship in a hospital environment in the COVID-19 pandemic context. Methods: This is an experience report, of a descriptive-reflective nature, about the experiences of four students attending the 9th semester of the Nursing course at a Public University from the state of Minas Gerais, during the Supervised Curricular Internship in a hospital environment in the COVID-19 pandemic context. Results: The initial practice in a hospital environment generated insecurity in the students, due to fear in the face of the current scenario of increased COVID-19 cases. The students experienced frustration in not providing dignified care to these patients and fear of contaminating themselves and being a means of spreading the virus to others. In addition, some students presented symptoms suggestive of mental distress. Conclusion: The leading role of the Nursing team was observed by the students when they witnessed, in their everyday lives, the set of actions provided for the assistance and care of patients aggravated by COVID-19. Despite the professionals' work overload and non-guarantee of rest between shifts, there was care continuity.